Epigenetic silencing of miR‐708 enhances NF‐κB signaling in chronic lymphocytic leukemia. Issue 6 (13th March 2015) - Baer, Constance; Oakes, Christopher C.; Ruppert, Amy S.; Claus, Rainer; Kim‐Wanner, Soo‐Zin; Mertens, Daniel; Zenz, Thorsten; Stilgenbauer, Stephan; Byrd, John C.; Plass, Christoph
<x xml:space="preserve">Abstract</x> MicroRNAs (miRNAs) are post‐transcriptional regulators of gene expression and their deregulation is involved in tumor development. Epigenetic gene silencing in cancer by DNA methylation contributes to the silencing of tumor‐suppressor genes, including miRNAs. We have recently shown that the promoter of miR‐708 is aberrantly methylated in chronic lymphocytic leukemia (CLL). To characterize the molecular signaling networks that are influenced by miR‐708, we performed a luciferase‐based screen evaluating the effects of ectopic miR‐708 expression on leukemia‐relevant signaling pathways. We found that miR‐708 strongly repressed NF‐κB signaling, a pathway known to be deregulated in CLL. Among the predicted miR‐708 targets was IKKβ (inhibitor of kappa light polypeptide gene enhancer in B cells, kinase‐β/IKBKB), a key kinase facilitating NF‐κB signaling. We validated the interaction of miR‐708 with the 3′‐untranslated region of IKKβ and found that miR‐708 overexpression represses endogenous IKKβ. Phosphorylation of the IKKβ target IκBα and expression of known NF‐κB target genes were impaired by miR‐708. Furthermore, we identified an enhancer region downstream of the miR‐708 promoter that displays a distinct DNA methylation status in CLL. High enhancer methylation is significantly correlated with lower miR‐708 expression and is predominantly found in patients with poor prognosis and shorter time to treatment. These results demonstrate that miR‐708 regulates the NF‐κB pathway by targeting IKKβ, and that methylation of a key enhancer region contributes to its suppression in CLL.